Laparoscopic augmentation of the diaphragmatic hiatus with biologic mesh versus suture repair: a systematic review and meta-analysis - Antoniou, Stavros A.; Müller, Beat P.; Antoniou, George A.; Köhler, Gernot; Luketina, Ruzica-Rosalia; Koch, Oliver O.; Pointner, Rudolph; Granderath, Frank A. (Langenbeck's archives of surgery, 2015)
Laparoscopic repair of large hiatal hernias is associated with high recurrence rates. Erosion and mesh migration are rare but devastating complications of synthetic mesh repair, whereas reoperation is accompanied by significant operative morbidity. The aim of this study was to estimate the comparative risk of hernia recurrence following primary suture or biologic mesh repair.
Gesehen am 27.07.2020